Two new species of the genus Niphargus Schiödte, 1849 (Amphipoda, fam. Niphargidae) from the Frasassi cave system in Central Italy - Karaman, Gordan S.; Borowsky, Betty; Dattagupta, Sharmishtha (Zootaxa, 2010)
Two new subterranean species of the genus Niphargus Schiödte, 1849 (Niphargus montanarius, n. sp. and N. frasassianus, n. sp. (Crustacea, Amphipoda, Gammaridea, Niphargidae) from the Frasassi cave system in Genga, the Marches, Italy, are described and figured, and their taxonomic status within the genus Niphargus is discussed.